Primary and Secondary Abscission in Pisum sativum and Euphorbia pulcherrima—How Do They Compare and How Do They Differ? - Hvoslef-Eide, Anne K.; Munster, Cristel M.; Mathiesen, Cecilie A.; Ayeh, Kwadwo O.; Melby, Tone I.; Rasolomanana, Paoly; Lee, YeonKyeong (Frontiers in Plant Science, 2016)
ABSTRACT Abscission is a highly regulated and coordinated developmental process in plants. It is important to understand the processes leading up to the event, in order to better control abscission in crop plants. This has the potential to reduce yield losses in the field and increase the ornamental value of flowers and potted plants. A reliable method of abscission induction in poinsettia (Euphorbia pulcherrima) flowers has been established to study the process in a comprehensive manner. By correctly decapitating buds of the third order, abscission can be induced in one week. AFLP differential display (DD) was used to search for genes regulating abscission. Through validation using qRT-PCR, more information of the genes involved during induced secondary abscission have been obtained. A study using two mutants of pea (Pisum sativum) in the def (Developmental funiculus) gene have been performed and compared these with wild type peas (tall and dwarf in both cases). The def mutant results in a deformed, abscission-less zone instead of normal primary abscission at the funiculus. RNA in situ hybridization studies using gene sequences from the poinsettia differential display, resulted in six genes differentially expressed for abscission specific genes in both poinsettia and pea. Two of these genes are associated with gene up- or down-regulation during the first two days after decapitation in poinsettia. Present and previous results in poinsettia (biochemically and gene expressions), enables a more detailed division of the secondary abscission phases in poinsettia than what has previously been described from primary abscission in Arabidopsis. This study compares the inducible secondary abscission in poinsettia and the non-abscising mutants/wild types in pea demonstrating primary abscission zones. The results may have wide implications on the understanding of abscission, since pea and poinsettia have been separated for 94-98 million years in evolution, hence any genes or processes in common are bound to be widespread in the plant kingdom.